Lung cancer survival and mortality in Taiwan following the initial launch of targeted therapies: an interrupted time series study. Issue 5 (10th May 2020) - Hsu, Jason C; Wei, Chen-Fang; Yang, Szu-Chun; Lin, Peng-Chan; Lee, Yang-Cheng; Lu, Christine Y
Abstract : Objectives: Two oral targeted therapies, gefitinib and erlotinib, were first approved and then launched into the market for treatment of late-stage non-small cell lung cancer (NSCLC) in Taiwan in 2003 and 2006, respectively. The aim of this study were to determine the trends in lung cancer burden and examine changes in lung cancer-related survival rates and mortality following the launch of these new drugs. Setting: Yearly lung cancer-related data (1994–2013), including incidence, number of newly diagnosed patients, survival rate and mortality, were retrieved from the Taiwan Cancer Registry Database. Design and outcome measures: Using a time series design with autoregressive integrated moving average model, we investigated and projected trends in the incidence and early diagnosis of lung cancer in Taiwan. We also estimated the changes in survival rates and mortality following the launch of targeted therapies using interrupted time series and segmented regression models. Results: The age-standardised incidence of lung cancer increased from 22.53 per 100 000 people in 1994 to 34.09 in 2013, and it was projected to reach 38.98 by 2020. The rate of early-stage NSCLC at diagnosis increased from 12.63% in 2004 to 23.99% in 2013, and it was projected to reach 32.95% by 2020. The 2-year lung cancer survival increased by 19.81% (95% CI 14.90% to 24.71%) 3 years following the launch of gefitinib. Lung cancer mortality declined by 5.97% (95% CI −8.20% to −3.73%) 3 years following the launch of gefitinib. Conclusions: Lung cancer survival rate increased and mortality decreased significantly following the launch of gefitinib and erlotinib in Taiwan.